Electrochemical device
By using a first activated carbon and a second activated carbon with a surface functional group amount difference of less than 0.14 meq/g in the electrochemical device and controlling the micropore and mesopore volumes, the capacity and floating charge characteristics problems were solved and efficient electrochemical performance was achieved.
Patent Information
- Application Number
- CN202380094739.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-13
- Filing Date
- 2023-11-02
- Publication Date
- 2025-10-03
AI Technical Summary
When two activated carbons with different pore distributions are combined, the capacity of the electrochemical device may become smaller and the floating charge characteristics may be easily deteriorated. In addition, the correlation between the pore distribution of activated carbon and the performance of the electrochemical device is not fully studied.
An electrochemical device is used, whose electrodes include a first activated carbon and a second activated carbon, the difference in the amount of surface functional groups between the two is less than 0.14 meq/g, and the cumulative volume ratio of micropores and mesopores is controlled to ensure good ion mobility and large capacity, thereby suppressing the deterioration of floating charge characteristics.
The capacity of the electrochemical device is improved and the deterioration of the floating charge characteristics is significantly suppressed, ensuring the long life and high efficiency performance of the electrode.
Smart Images

Figure CN120752719A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This disclosure claims the benefit of priority from Japanese Patent Application No. 2023-038316, filed with the Japan Patent Office on March 13, 2023, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0002] The present invention relates to an electrochemical device including an electrode including a first activated carbon and a second activated carbon in the configuration of the electrode layer. Background Art
[0003] An electrochemical device comprises a pair of electrodes and an electrolyte, with at least one of the electrodes containing an active material capable of absorbing and desorbing ions. Electric double-layer capacitors, an example of an electrochemical device, offer a longer lifespan, faster charging, and superior output characteristics compared to secondary batteries, making them widely used in backup power supplies and other applications.
[0004] The active material of the electrochemical device uses, for example, porous carbon particles (hereinafter referred to as activated carbon) obtained by carbonizing and activating raw materials such as coconut shells. Various studies have been conducted on activated carbon. For example, in Patent Document 1, it is proposed to use two activated carbons with different pore distributions as electrode materials for double-layer capacitors. Specifically, a double-layer capacitor electrode material is proposed in which a first activated carbon and a second activated carbon having different peak positions in the pore size distribution (specifically, the differential pore volume distribution) are mixed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 2008-108979 Summary of the Invention
[0008] Problems to be solved by the invention
[0009] However, as mentioned above, when combining two activated carbons with different pore distributions, the capacity of the electrochemical device may decrease and the float charge characteristics may deteriorate depending on the combination. However, research on the correlation between the pore distribution of activated carbon and the performance of electrochemical devices is still insufficient.
[0010] Means for solving problems
[0011] In view of the above situation, one aspect of the present invention relates to an electrochemical device comprising a pair of electrodes and an electrolyte, at least one of the pair of electrodes comprising a current collector and an active layer disposed on the surface of the current collector, the active layer comprising a first activated carbon and a second activated carbon, and the difference between the amount of surface functional groups of the first activated carbon and the amount of surface functional groups of the second activated carbon is less than 0.14 meq / g.
[0012] Effects of the Invention
[0013] According to the present invention, the capacity of an electrochemical device can be increased while suppressing deterioration of floating charge characteristics.
[0014] The novel features of the present invention are described in the appended claims, but both the configuration and content of the present invention, together with other objects and features of the present invention, will be better understood from the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a partially cutaway perspective view of an electrochemical device according to one embodiment of the present invention. DETAILED DESCRIPTION
[0016] Hereinafter, examples are given to illustrate the embodiments of the present disclosure, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values, materials, etc. are sometimes illustrated, but other numerical values, materials, etc. may also be applied as long as the effects of the present disclosure can be obtained. In addition, well-known constituent elements may also be applied to constituent elements other than the characteristic parts of the present disclosure. In this specification, when referring to the "range of numerical values A to numerical values B", the range includes numerical values A and numerical values B.
[0017] In the following description, when lower limits and upper limits of numerical values related to specific physical properties, conditions, etc. are exemplified, any of the exemplified lower limits and any of the exemplified upper limits can be arbitrarily combined as long as the lower limit is not greater than the upper limit. When multiple materials are exemplified, unless otherwise specified, one type can be selected and used alone, or two or more types can be used in combination.
[0018] Furthermore, the present disclosure includes combinations of matters described in two or more claims arbitrarily selected from the plurality of claims recited in the appended claims. That is, as long as no technical contradiction arises, matters described in two or more claims arbitrarily selected from the plurality of claims recited in the appended claims may be combined.
[0019] An electrochemical device according to one embodiment of the present invention comprises a pair of electrodes and an electrolyte. At least one of the pair of electrodes comprises a current collector and an active layer provided on the surface of the current collector, the active layer comprising a first activated carbon and a second activated carbon. When ions are adsorbed on the activated carbon in the electrolyte, a double electric layer is formed, exhibiting capacity. When ions are desorbed from the activated carbon, a non-Faraday current flows. The electrodes provided in the electrochemical device according to this embodiment utilize such a phenomenon. In the electrodes provided in the electrochemical device according to this embodiment, the difference between the amount of surface functional groups of the first activated carbon and the amount of surface functional groups of the second activated carbon is less than 0.14 meq / g. By this configuration, the floating charge characteristics can be improved.
[0020] Furthermore, float charge performance is an indicator of the degree of degradation of an electrochemical device during float charging, maintained at a constant voltage using an external DC power supply. The smaller the capacity drop during float charge, the better the float charge performance. This capacity drop is caused by the decomposition of the electrolyte during float charge. Therefore, the smaller the amount of gas generated during electrolyte decomposition, the better the float charge performance.
[0021] When the difference between the surface functional group amounts of the first and second activated carbons is less than 0.14 meq / g, an electrochemical device with excellent float charge characteristics can be obtained. On the other hand, if the difference between the surface functional group amounts of the first and second activated carbons is greater than 0.14 meq / g, float charge characteristics may deteriorate. The detailed reason for this is not clear, but it is believed to be due to an increase in gas generation associated with the decomposition of the electrolyte.
[0022] The difference between the amount of surface functional groups of the first activated carbon and the amount of surface functional groups of the second activated carbon may be 0.13 meq / g or less, 0.12 meq / g or less, or 0.11 meq / g or less. Furthermore, the lower limit of the difference between the amount of surface functional groups of the first activated carbon and the amount of surface functional groups of the second activated carbon is 0.00 meq / g.
[0023] The first activated carbon obtained by the MP method has a The cumulative volume of pores with a pore diameter of 0.5 cm (hereinafter also referred to as micropores) is 3 / g or more, and the BJH method has Above and The cumulative volume of pores with a pore diameter of 0.5 cm or less (hereinafter also referred to as mesopores) is 0.5 cm 3 / g or less, the cumulative volume of the micropores of the second activated carbon is 1.0 cm 3 / g or less, and the cumulative volume of the mesopores is 0.25cm 3 / g or above.
[0024] In the first activated carbon, the micropores and mesopores satisfying the above-mentioned relationship help to increase the specific surface area of the active layer as a whole, and thus the main impact on the capacity (especially the initial capacity) becomes larger. On the other hand, in the second activated carbon, the micropores and mesopores satisfying the above-mentioned relationship help to increase the mobility of ions in the electrolyte in the pores, and thus the main impact on the floating charge characteristics becomes larger. In addition, in the second activated carbon, the micropores and mesopores satisfying the above-mentioned relationship also help to increase the specific surface area of the active layer as a whole. That is, by making the micropores and mesopores in the second activated carbon satisfy the above-mentioned relationship, the ions in the electrolyte can easily diffuse in the pores, the pores are not easily clogged, and good ion movement can be ensured. Therefore, not only the floating charge characteristics are improved, but also the specific surface area of the active layer as a whole is easily increased, and therefore a large initial capacity is easily obtained.
[0025] That is, by making the micropores and mesopores in the first activated carbon and the second activated carbon satisfy the above-mentioned relationship, a large number of micropores and mesopores are ensured in the entire active layer, thereby obtaining a large capacity and further improving the floating charge characteristics.
[0026] In the first activated carbon, the micropores may have a size of 0.6 cm 3 / g or more, and can also have a cumulative volume of 0.7cm 3 / g or more of cumulative volume. In the first activated carbon, the micropores may have a size of 1.2 cm 3 / g or less, and can also have a cumulative volume of 1.1cm 3 / g or less, and can also have a 1.0cm 3 / g or less cumulative volume.
[0027] In the second activated carbon, the micropores may have a size of 0.3 cm 3 / g or more, and can also have a cumulative volume of 0.4cm 3 / g or more of cumulative volume. In the second activated carbon, the micropores may have a size of 0.95 cm 3 / g or less cumulative volume.
[0028] In the first activated carbon, the mesopores may have a size of 0.10 cm 3 / g or more, and can also have a cumulative volume of 0.11cm 3 / g or more, and can also have a cumulative volume of 0.15cm 3 / g or more, and can also have a cumulative volume of 0.20cm 3 / g or more of cumulative volume. In the first activated carbon, the mesopores may have a size of 0.50 cm 3 / g or less, and can also have a cumulative volume of 0.45cm 3 / g or less cumulative volume.
[0029] In the second activated carbon, the mesopores may have a size of more than 0.50 cm 3 / g of cumulative volume, and can also have a volume of 0.55cm 3 / g or more. In the second activated carbon, the mesopores may have a size of 0.70 cm 3 / g or less, and can also have a cumulative volume of 0.65cm 3 / g or less cumulative volume.
[0030] The surface functional group amount of the first activated carbon is preferably greater than or equal to 0.05 meq / g and less than or equal to 0.4 meq / g, and the surface functional group amount of the second activated carbon is preferably greater than or equal to 0.05 meq / g and less than or equal to 0.4 meq / g. The upper limit of the surface functional group amount of the first activated carbon may be 0.35 meq / g, 0.30 meq / g, 0.25 meq / g, or 0.20 meq / g. The lower limit of the surface functional group amount of the second activated carbon may be 0.10 meq / g, and the upper limit of the surface functional group amount of the second activated carbon may be 0.30 meq / g, or 0.20 meq / g.
[0031] Hydrophilic surface functional groups such as carboxyl, hydroxyl, and quinone groups on the surface of activated carbon can sometimes promote decomposition reactions in the electrolyte, generating gas internally. This generated gas can become trapped between the electrodes, reducing the opposing area and potentially deteriorating float charge performance. On the other hand, by limiting the surface functional group amounts of the first and second activated carbons to the above range, gas generation during float charge can be significantly suppressed, significantly preventing a degradation in float charge performance.
[0032] The amount of surface functional groups on the first activated carbon is preferably less than that on the second activated carbon. With this configuration, even if gas is generated from the mesopores of the second activated carbon, it is adsorbed in the micropores of the first activated carbon, making it difficult for the gas to diffuse into the cells. This can thus suppress deterioration of the float charge characteristics. However, adsorption of gas generated by the first activated carbon in the micropores of the second activated carbon can also suppress gas diffusion, but the former is more effective.
[0033] The ratio of the mass of the first activated carbon to the total mass of the first activated carbon and the second activated carbon is preferably 20 to 80 mass %. By setting it within this range, a large capacity and excellent float charge characteristics can be easily obtained compared to the case of using a single type of activated carbon.
[0034] The above-mentioned determination of the amount of surface functional groups can be implemented as follows. Specifically, first, use activated carbon as a sample, dry the sample in a dryer adjusted to a temperature of 130°C ± 5°C for more than 16 hours, and naturally cool the sample taken out of the dryer in a desiccator for more than 20 minutes. Next, collect a sample of about 2g ± 0.01g. At this time, measure to the decimal point of 0.1mg. Place the measured sample in a 100cm 3 Then, add 50cm 3 A 0.1 mol / l NaOH solution was used as the reagent. The conical flask containing the sample and reagent was stirred continuously for 2 hours using a stirrer and then allowed to stand for 22 hours. After standing, the mixture was filtered using 5 types of filter paper C to obtain a filtrate. The filtrate was placed in a beaker 25 cm 3 While stirring the filtrate with a stirrer, the filtrate is titrated with an aqueous HCl solution having a concentration of 0.1 mol / l using an automatic titrator. At this point, the titration is terminated when the pH of the filtrate reaches 4.0, and the total titration amount t1 from the start to the end of the titration is measured. Next, a NaOH solution of the above concentration and volume without the addition of a sample is titrated in the same manner, and the total titration amount t2 until the pH reaches 4.0 is measured (blank test). Then, using the values of t1 and t2, the surface functional group amount is calculated using the following formula (1).
[0035] Surface functional group amount = 0.1 × (t2-t1) (1)
[0036] The pore volume of the activated carbon is determined by measuring the pore distribution of the activated carbon sample. To collect samples from electrochemical devices, an unused or early-stage electrochemical device in a fully discharged state is disassembled to remove the electrodes, and the active layer is peeled from the current collector. This is then pulverized to obtain a sample (particle group), which is then heat-dried at 150°C for measurement.
[0037] The pore distribution is measured by a gas adsorption method using nitrogen. The measuring device is, for example, the automatic specific surface area / pore distribution measuring device "Tristar II 3020" manufactured by Shimadzu Corporation. It should be noted that in order to remove impurities, the sample is pre-treated under heating vacuum exhaust (for example, 250°C, 50mTorr or less) before measurement. In the analysis of the pore distribution, the BJH method (Barrett-Joyner-Halenda method) is used, and in the BJH method, the Harkins & Jura formula is used. Using the cumulative pore volume distribution obtained by the BJH method, the volume (cm 3On the other hand, in the MP method (Micropore method), the distribution of micropores and the volume (cm2) of the micropores are determined using "t-plot" (BC Lippens, JH de Boer, J. Catalysis, 4319 (1965)). 3 ).
[0038] It should be noted that samples collected from electrochemical devices may contain binders and conductive agents in addition to activated carbon. However, the amount of binders, etc., is small and has little effect on the pore distribution of the activated carbon. Specifically, the shape of the cumulative pore volume distribution curve of the sample collected from the electrochemical device is almost the same as that of the sample collected from the activated carbon alone. Compared with the sample collected from the activated carbon alone, the cumulative pore volume distribution curve is slightly shifted downward (the cumulative volume is slightly smaller).
[0039] Activated carbon can be produced by, for example, carbonizing the raw material by heat treatment and activating the obtained carbide to make it porous. As raw materials, for example, wood, coconut shell, waste pulp liquid, coal or coal-based asphalt obtained by thermal decomposition thereof, heavy oil or petroleum-based asphalt obtained by thermal decomposition thereof, phenolic resin, petroleum coke, coal coke, etc. can be cited. As activation treatment, for example, gas activation using gases such as water vapor and activation using alkalis such as potassium hydroxide can be cited. The activated carbon obtained by the above-mentioned activation treatment can be pulverized. After the pulverization treatment, classification treatment can be carried out. The pulverization treatment uses, for example, a ball mill, a jet mill, etc.
[0040] Activated carbon is obtained, for example, by pulverizing and granulating carbonized coconut shells to obtain a pulverized product, and then subjecting the pulverized product to an activation treatment. Alternatively, activated carbon is obtained, for example, by kneading finely pulverized coal with a binder such as coal tar or pitch, compression-molding the resulting kneaded product to obtain a molded product, and then pulverizing and granulating the molded product to obtain a pulverized product, followed by heat treatment and activation.
[0041] The pore distribution of activated carbon can be adjusted by adjusting the raw materials, heat treatment temperature, activation temperature in gas activation, degree of pulverization, etc. Activated carbon is used by mixing two or more types.
[0042] As described above, the electrochemical device of the present embodiment comprises a pair of electrodes and an electrolyte. At least one of the pair of electrodes includes a current collector and an active layer provided on the surface of the current collector. The active layer includes a first activated carbon and a second activated carbon. In addition to the first activated carbon and the second activated carbon, the active layer may also include a binding material and a conductive material. That is, the active layer can be formed by a mixture (composite material) of the first activated carbon, the second activated carbon, the binding material and the conductive material. In the case where the active layer is formed by a composite material, the proportion of activated carbon in the active layer is, for example, 88% by mass or more.
[0043] Examples of the binder include resin materials such as polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC) (including alkali metal salts and ammonium salts of CMC), and styrene-butadiene rubber (SBR). Examples of the conductive agent include carbon black such as acetylene black.
[0044] The electrodes are obtained, for example, by applying a slurry containing activated carbon, a binder, a conductive agent, and a dispersion medium to the surface of a current collector to form a coating film, and then drying and rolling the coating film to form an active layer.
[0045] As electrochemical devices, electric double layer capacitors (EDLCs), lithium ion capacitors (LICs), and the like can be cited. When the electrochemical device is an EDLC, at least one of a pair of electrodes can use the above-mentioned electrode comprising activated carbon. When the electrochemical capacitor is an EDLC, both of a pair of electrodes can be the above-mentioned electrodes comprising activated carbon. When the electrochemical device is a LIC, the above-mentioned electrode comprising activated carbon can be used on one side (positive electrode) of a pair of electrodes, and the negative electrode used in a lithium ion secondary battery can be used on the other side (negative electrode) of a pair of electrodes. The negative electrode used in a lithium ion secondary battery, for example, comprises a negative electrode active material (such as graphite) capable of intercalating and deintercalating lithium ions.
[0046] The electrolyte solution contains a solvent (non-aqueous solvent) and an ionic substance. The ionic substance is dissolved in the solvent and contains cations and anions. The ionic substance can include, for example, a low-melting-point compound (ionic liquid) that can exist as a liquid at around room temperature. The concentration of the ionic substance in the electrolyte solution is, for example, 0.5 mol / L or more and 2.0 mol / L.
[0047] As the solvent, a high-boiling-point solvent is preferred. Examples of the solvent include lactones such as γ-butyrolactone, carbonates such as propylene carbonate, polyols such as ethylene glycol and propylene glycol, cyclic sulfones such as sulfolane, amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, and formaldehyde.
[0048] Ionic substances include, for example, organic salts. An organic salt refers to a salt in which at least one of the anion and the cation contains an organic substance. Examples of organic salts in which the cation contains an organic substance include quaternary ammonium salts. Examples of organic salts in which the anion (or zwitterion) contains an organic substance include trimethylammonium maleate, triethylammonium borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, and mono-1,3-dimethyl-2-ethylimidazolinium phthalate.
[0049] From the viewpoint of improving the withstand voltage characteristics, the anion preferably includes an anion of a fluorine-containing acid. Examples of the anion of a fluorine-containing acid include BF4 - and / or PF6 - The organic salt preferably contains, for example, a tetraalkylammonium cation and a fluorine-containing acid anion. Specifically, diethyldimethylammonium tetrafluoroborate (DEDMABF4) and triethylmethylammonium tetrafluoroborate (TEMABF4) can be cited.
[0050] A separator is preferably placed between the pair of electrodes. The separator is ion-permeable and serves to physically separate the pair of electrodes to prevent short circuits. Examples of the separator include nonwoven fabrics primarily composed of cellulose, glass fiber mats, and microporous membranes made of polyolefins such as polyethylene.
[0051] Below, refer to Figure 1 An electrochemical device according to an embodiment of the present invention will be described. Figure 1 This is a perspective view of a partially cutaway electrochemical device according to an embodiment of the present invention. Figure 1 electrochemical devices.
[0052] Figure 1 The electrochemical device 10 is an electric double-layer capacitor having a wound capacitor element 1. The capacitor element 1 is composed of a first electrode 2 and a second electrode 3 in the form of a sheet wound together with a separator 4 interposed therebetween. The first electrode 2 and the second electrode 3 respectively have a first current collector and a second current collector made of metal, and a first active layer and a second active layer supported on their surfaces, and exhibit capacitance by adsorbing and desorbing ions.
[0053] The current collector uses, for example, aluminum foil. The surface of the current collector can be roughened by etching or other methods. The separator 4 uses, for example, a non-woven fabric with cellulose as the main component. A first lead 5a and a second lead 5b are connected to the first electrode 2 and the second electrode 3, respectively, as lead-out parts. The capacitor element 1 is housed in a cylindrical outer casing 6 together with an electrolyte (not shown). The material of the outer casing 6 can be, for example, aluminum, stainless steel, copper, iron, brass or other metals. The opening of the outer casing 6 is sealed by a sealing member 7. The leads 5a and 5b are led out to the outside in a manner that passes through the sealing member 7. The sealing member 7 uses, for example, a rubber material such as butyl rubber.
[0054] In the above embodiment, a wound-type capacitor is described. However, the scope of application of the present invention is not limited thereto, and the present invention can also be applied to capacitors of other structures, such as a laminated or coin-type capacitor.
[0055] (Note)
[0056] The following technologies are disclosed through the above description.
[0057] (Technique 1)
[0058] An electrochemical device comprising a pair of electrodes and an electrolyte, wherein at least one of the pair of electrodes comprises a current collector and an active layer disposed on a surface of the current collector, the active layer comprising a first activated carbon and a second activated carbon, and the difference between the amount of surface functional groups of the first activated carbon and the amount of surface functional groups of the second activated carbon is less than 0.14 meq / g.
[0059] (Technique 2)
[0060] The electrochemical device according to technology 1, wherein the first activated carbon is obtained by the MP method and has a The cumulative volume of the pores with a pore diameter of 0.5 cm 3 / g or more, and the BJH method has Above and The cumulative volume of pores with a pore diameter of 0.5 cm 3 / g or less, the second activated carbon obtained by the MP method has a The cumulative volume of pores with a pore diameter of 1.0 cm 3 / g or less, and the BJH method has Above and The cumulative volume of pores with a pore diameter of 0.25 cm 3 / g or above.
[0061] (Technique 3)
[0062] The electrochemical device according to technology 1 or 2 is characterized in that the amount of surface functional groups of the first activated carbon is less than the amount of surface functional groups of the second activated carbon.
[0063] (Technique 4)
[0064] The electrochemical device according to any one of techniques 1 to 3, wherein the surface functional group amount of the first activated carbon is 0.05 meq / g to 0.4 meq / g, and the surface functional group amount of the second activated carbon is 0.05 meq / g to 0.4 meq / g.
[0065] (Technique 5)
[0066] The electrochemical device according to any one of techniques 1 to 4, wherein a ratio of the mass of the first activated carbon to the total mass of the first activated carbon and the second activated carbon is 20 to 80 mass %.
[0067] While the present invention has been described with respect to currently preferred embodiments, such disclosure should not be construed in a limiting sense. Upon reading the above disclosure, various modifications and variations will undoubtedly be apparent to those skilled in the art in the art to which the present invention pertains. Therefore, it should be construed that the appended claims encompass all such modifications and variations without departing from the true spirit and scope of the present invention.
[0068] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to the examples.
[0069] Examples 1 to 3, Comparative Examples 1 to 2, and Reference Examples 1 to 5
[0070] As an electrochemical device, a wound-type electric double-layer capacitor with a rated voltage of 2.7 V was produced. A specific method for producing the electrochemical device will be described below.
[0071] (Electrode Preparation)
[0072] 88 parts by mass of active material, 2 parts by mass of polytetrafluoroethylene, 4 parts by mass of an ammonium salt of carboxymethyl cellulose swellable in water (solid content ratio 5% by mass), and 6 parts by mass of acetylene black were dispersed in water to prepare a slurry. The resulting slurry was applied to an aluminum foil to form a coating film, which was then vacuum-dried at 110°C and rolled to form an active layer, thereby producing an electrode.
[0073] (Preparation of Electrolyte)
[0074] An electrolyte solution was prepared by dissolving diethyldimethylammonium tetrafluoroborate (DEDMABF4) in γ-butyrolactone (GBL). The concentration of DEDMABF4 in the electrolyte solution was set to 1.0 mol / L.
[0075] (Fabrication of Electrochemical Devices)
[0076] Prepare a pair of electrodes, connect leads to each, and wind them together with a cellulose nonwoven fabric separator to form a capacitor element. This capacitor element, along with the electrolyte, is placed in a specified outer casing and sealed with a sealing member to complete the electrochemical device (electric double-layer capacitor). Then, while applying the rated voltage, perform an aging treatment at 60°C for 5.5 hours.
[0077] In the production of the electrodes, an active material in which the first activated carbon and the second activated carbon were mixed at a predetermined mass ratio was used to obtain electrodes x1 to x3 (see Table 2 below). Examples 1 to 3 are electrochemical devices including a pair of electrodes x1 to x3.
[0078] Using an active material obtained by mixing the first activated carbon and the second activated carbon at a predetermined mass ratio, y1 to y2 were obtained (see Table 2 below). Comparative Examples 1 and 2 are electrochemical devices each including a pair of electrodes y1 to y2.
[0079] For reference, electrodes s1 to s5 were obtained using only one type of activated carbon (see Table 1 below). Reference Examples 1 to 5 are electrochemical devices including a pair of electrodes s1 to s5.
[0080] Table 1 shows data on the micropore volume and mesopore volume, and the amount of surface functional groups of the activated carbon used in the active layer of each electrode included in the electrochemical devices of Reference Examples 1 to 5.
[0081] [Table 1]
[0082]
[0083] Table 2 shows the combination, mass ratio, and difference in surface functional group amount of the first activated carbon and the second activated carbon contained in the active layer of each electrode included in the electrochemical devices of Examples 1 to 3 and Comparative Examples 1 and 2.
[0084] [Table 2]
[0085]
[0086] The following evaluations were performed on each of the electrochemical devices obtained above.
[0087] [evaluate]
[0088] (Measurement of Initial Capacity (Before Float Charge Test) of Electrochemical Devices)
[0089] At -30°C, constant current charging was performed at 200 mA until the voltage reached 2.35 V, and the voltage of 2.35 V was maintained for 7 minutes. Then, constant current discharge was performed at 100 mA until the voltage reached 0 V at -30°C.
[0090] During the above discharge, the time t (sec) required for the voltage to drop from 2.0 V to 1.6 V was measured. Note that 2.0 V is equivalent to 85% of 2.35 V (the voltage at full charge), and 1.6 V is equivalent to 68% of 2.35 V. Using the measured time t, the capacity (initial capacity) C1(F) of the electrochemical device before the float charge test was calculated using the following formula (2).
[0091] Capacity C1=Id×t / V(2)
[0092] In the formula (1), Id is the current value during discharge (0.01 A), and V is the value obtained by subtracting 1.6 V from 2.0 V (0.4 V).
[0093] (Float Charge Test of Electrochemical Devices)
[0094] At 50°C, constant current charging was performed at a current of 100 mA until the voltage reached 2.7 V, and then the voltage was maintained at 2.7 V for 4000 hours. The electrochemical device was stored while applying a voltage of 2.7 V. Subsequently, constant current discharge was performed at 20 mA at 25°C until the voltage reached 0 V.
[0095] (Capacity Measurement of Electrochemical Devices After Float Charge Test)
[0096] Then, the electrochemical device was charged and discharged in a -30°C environment in the same manner as before the float test, and the capacity C2(F) after the float test was determined. The capacity C2(F) was determined according to (2) above.
[0097] (Measurement of the Slope of Capacity Change)
[0098] Using the capacity C1 and capacity C2 of the electrochemical device obtained above before and after the float test, the slope of the capacity change (hereinafter also referred to as the capacity change slope) is calculated by the following formula (3). The smaller the capacity change slope, the more suppressed the reduction in capacity after the float test. It should be noted that in formula (3), T is the time (2000 hr) of the float charge during the float test.
[0099] Capacity change slope = |(C2 / C1-1)×100 / (T 1 / 2 )| (3)
[0100] Table 3 shows the evaluation results of Reference Examples 2 and 4, each including a pair of electrodes s2 and s4 using activated carbon B or activated carbon D, respectively, and the evaluation results of Example 1, including a pair of electrodes x1 containing activated carbon B as the first activated carbon and activated carbon D as the second activated carbon.
[0101] The capacity change slope of Example 1 was greater than that of Reference Examples 2 and 4, suppressing capacity degradation. Example 1 exhibited better float charge characteristics than Reference Examples 2 and 4, which each used a pair of electrodes s2 and s4 containing either the first activated carbon (activated carbon B) or the second activated carbon (activated carbon D) contained in electrode x1.
[0102] [Table 3]
[0103]
[0104] Table 4 shows the evaluation results of Reference Examples 1 and 4, each including a pair of electrodes s1 and s4 using activated carbon A or activated carbon D, respectively, and Example 2, including a pair of electrodes x2 containing activated carbon A as the first activated carbon and activated carbon D as the second activated carbon.
[0105] The capacity change slope of Example 2 was greater than that of Reference Examples 1 and 4, suppressing capacity degradation. Example 2 exhibited better float charge characteristics than Reference Examples 1 and 4, which each used a pair of electrodes s1 and s4 containing either the first activated carbon (activated carbon A) or the second activated carbon (activated carbon D) contained in electrode x2.
[0106] [Table 4]
[0107]
[0108] Table 5 shows the evaluation results of Reference Examples 1 and 5, each including a pair of electrodes s1 and s5 using activated carbon A or activated carbon E, respectively, and Example 3, including a pair of electrodes x3 containing activated carbon A as the first activated carbon and activated carbon E as the second activated carbon.
[0109] The capacity change slope of Example 3 was greater than that of Reference Examples 1 and 5, suppressing capacity degradation. Example 3 exhibited better float charge characteristics than Reference Examples 1 and 5, which each used a pair of electrodes s1 and s5 containing either the first activated carbon (activated carbon A) or the second activated carbon (activated carbon E) contained in electrode x3.
[0110] [Table 5]
[0111]
[0112] Table 6 shows the evaluation results of Reference Examples 3 and 4, each including a pair of electrodes s3 and s4 using activated carbon C or activated carbon D alone, and the evaluation results of Comparative Example 1, including a pair of electrodes y1 containing activated carbon C as the first activated carbon and activated carbon D as the second activated carbon.
[0113] The capacity change slope of Comparative Example 1 was between the values of Reference Examples 3 and 4. Comparative Example 1 was unable to obtain float charge characteristics that were two levels better than those of Reference Examples 3 and 4, which had a pair of electrodes s3 and s4 each using only the first activated carbon (activated carbon C) or the second activated carbon (activated carbon D) contained in the electrode y1.
[0114] [Table 6]
[0115]
[0116] Table 7 shows the evaluation results of Reference Examples 3 and 5, each of which includes a pair of electrodes s3 and s5 using activated carbon C or activated carbon E alone, and the evaluation results of Comparative Example 2, which includes a pair of electrodes y2 containing activated carbon C as the first activated carbon and activated carbon E as the second activated carbon.
[0117] The capacity change slope of Comparative Example 2 was between that of Reference Example 3 and Reference Example 4. Comparative Example 2 was unable to obtain float charge characteristics that were two levels better than those of Reference Example 3 and Reference Example 5, which had a pair of electrodes s3 and s5 each using the first activated carbon (activated carbon C) or the second activated carbon (activated carbon E) contained in the electrode y2.
[0118] [Table 7]
[0119]
[0120] As can be seen from the above, in Examples 1 to 3, the difference in the amount of surface functional groups of the first activated carbon and the second activated carbon contained in the active layer of each electrode is less than 0.14 meg / g, so a large capacity and excellent floating charge characteristics can be obtained.
[0121] Industrial Applicability
[0122] The electrochemical device of the present invention is suitable for applications requiring large capacity and excellent floating charge characteristics.
[0123] Reference numerals
[0124] 1: Capacitor element, 2: First electrode, 3: Second electrode, 4: Separator, 5a: First lead, 5b: Second lead, 6: External case, 7: Sealing member, 10: Electrochemical device.
Claims
1. An electrochemical device comprising a pair of electrodes and an electrolyte, At least one of the pair of electrodes includes a current collector and an active layer provided on a surface of the current collector. The active layer comprises a first activated carbon and a second activated carbon, The difference between the amount of surface functional groups of the first activated carbon and the amount of surface functional groups of the second activated carbon is less than 0.14 meq / g.
2. The electrochemical device according to claim 1, wherein The first activated carbon obtained by the MP method has a The cumulative volume of the pores with a pore diameter of 0.5 cm 3 / g or more, and the BJH method has Above and The cumulative volume of pores with a pore diameter of 0.5 cm 3 / g or less, The second activated carbon obtained by the MP method has a value less than The cumulative volume of pores with a pore diameter of 1.0 cm 3 / g or less, and the BJH method has Above and The cumulative volume of pores with a pore diameter of 0.25 cm 3 / g or above.
3. The electrochemical device according to claim 2, characterized in that The amount of surface functional groups of the first activated carbon is less than that of the second activated carbon.
4. The electrochemical device according to claim 2 or 3, wherein The surface functional group amount of the first activated carbon is 0.05 meq / g or more and 0.4 meq / g or less, and the surface functional group amount of the second activated carbon is 0.05 meq / g or more and 0.4 meq / g or less.
5. The electrochemical device according to claim 4, wherein The ratio of the mass of the first activated carbon to the total mass of the first activated carbon and the second activated carbon is 20 to 80 mass %.
Citation Information
Patent Citations
Electrode material for electric double layer capacitor and manufacturing method thereof
JP2008108979A
Determination device, encoding device, decoding device, and program
JP2023038316A